Nurse-Led intervention on knowledge, attitude and beliefs of Acute Coronary Syndrome - Sukhbeer K Darsin Singh; Ahmad Aldrie Amir; Rahmat Nasrah; Nant Thin Thin Hmwe (Blackwell Publishing Ltd, 2016)
Background